Financial Factors and Corporate Governance Affecting the Sukuk Rating - Aditya Yoshua; Nadia Asandimitra (Profesional Muda Cendekia Publishing, 2021)
The development of corporate Sukuk in recent years has continued to show a significant increase in both the number of Sukuk issuers and investors of Sukuk instruments. This study aims to identify the determinants of financial factors and corporate governance factors on the Sukuk rating. The type of data used in this research is quantitative data from secondary sources. The purposive sampling method is used with criteria specifically non-financial companies issuing Sukuk circulating on the IDX and Sukuk ratings were issued by PT Pefindo. The data consist of 93 Sukuk issuances from 2010 to 2019. Ordinal logistic regression model with SPSS version 26 is then used to ascertain the significant determinants of Sukuk rating. This study found that financial factors such as liquidity, leverage, profitability, and firm size affect the Sukuk rating. However, company growth does not affect the Sukuk rating because the growth of company assets is not followed by the growth of intangible assets such as the quality of human resources. Corporate governance factors that affect the Sukuk rating are managerial ownership and independent commissioners. Meanwhile, the audit committee does not affect the Sukuk rating because the number of audit committee members does not increase the company's performance.